Failed persuasion: the linguistic dynamics of dpr’s public addresses and their role in escalating civil unrest - Sitinjak, Vivi Novalia; Silalahi, Rachael Joy N; Ersan, Ronaldo; Ardauli, Cindy (Lembaga Riset Mutiara Akbar, 2026)
This study examines the failure of political persuasion in public discourse by examining the language strategies used in statements by members of the Indonesian House of Representatives (DPR) during the civil unrest on August 25–28, 2025. Using a Critical Discourse Analysis (CDA) approach, this study analyzes how word choice, expressions of judgment, use of modality, and ideological positions in political speech actually fuel public anger rather than producing a persuasive effect. The research data includes verified public statements, media transcripts, and official quotations circulating during the escalation period. The results show that the failure of persuasion occurred due to a discursive mismatch between elite political narratives and the socio-economic conditions of society. These findings enrich the study of political discourse by viewing the failure of persuasion as a linguistic process influenced by power imbalances, lack of context sensitivity, and ideological differences.